Ubiquitous Power Internet of Things-Oriented Low-Latency Edge Task Scheduling Optimization Strategy - Liang, Yu; Li, Taoshen (Frontiers in Energy Research, 2022)
This paper studies an UPIoT smart sensing network edge computing model and an improved multi node cluster cooperative scheduling optimization strategy. The cluster server is added to the edge aware computing network, and an improved low delay edge task collaborative scheduling algorithm (LLETCS) is designed by using the vertical cooperation and multi node cluster collaborative computing scheme between edge aware networks. Then the problem is transformed based on linear reconstruction technology, and a parallel optimization framework for solving the problem is proposed.